IMPLEMENTATION OF DISTRICT MINIMUM WAGE POLICY AT THE DEPARTMENT OF MANPOWER AND TRANSMIGRATION SUKABUMI DISTRICT - Devi Topyani; Andi Mulyadi; Rizki Hegia Sampurna (DIA: Jurnal Administrasi Publik, 2023)
This study aims to determine the implementation of the minimum wage policy in Sukabumi Regency. This study uses qualitative research methods with a descriptive approach. It consists of four informants divided into two groups: informants who implement policy and policy implementers who are target informants; data collection techniques using observation techniques, interviews, and documentation; data analysis using flow models; and data validation using triangulation and triangulation techniques. This study uses four policy implementation variables from George Orwell's The Wealth of Nations. The results of this study indicate that the implementation of minimum wage policy in Sukabumi Regency goes well in the dimensions of communication and disposition, but in the dimensions of resources and bureaucratic structure is not optimal, this is because the resources with the refocusing of the budget and the number of employees and infrastructure needed optimization and the bureaucratic structure is not the authority of the Department of manpower and Transmigration Sukabumi to assess how the SOP's related to the District Minimum wage and its implementation mechanism, it is because the Minimum wage policy of the City / District: 561 / PP.732-Kesra/2021 so that it is regulated by the province regarding sop's and the implementation mechanism